Analisa Bisnis Ekonomi Kreatif Sub Sektor Fashion Untuk Meningkatkan Kepatuhan Wajib Pajak ( Studi Kasus Pada Pelaku Ekonomi Kreatif Di Kabupaten Malang ) - Fitria Dewi; Jeni Susyanti; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstrackThe purpose of this study is to analyze the creative economy entrepreneurs in Indonesia in the fashion sub-sector to meet taxpayer compliance. The population in this study were 500 creative economy entrepreneurs in the fashion sector in Malang Regency. Because the population is large, samples taken in accordance with the characteristics of respondents are taken 10% of the 500 are 50 respondents. This study uses a quantitative approach. Data testing techniques used in this study include data instrument testing (validity and reliability), normality test, and simple linear regression test. The analysis shows that the creative economy business in the fashion sub-sector has high tax compliance, it was found that as many as 56% of the creative economy business people in the fashion sub-sector in Malang experienced business development. And seen from several measurement indicators that can increase taxpayer compliance. So that the creative economy business executor of the fashion sub-sector complies with business tax payments. Keywords: creative economic, fashion, taxpayer compliance